SEC24C deficiency causes trafficking and glycosylation abnormalities in an epileptic encephalopathy with cataracts and dyserythropoeisis - Bögershausen, Nina; Cavdarli, Büsranur; Nagai, Taylor H.; Milev, Miroslav P.; Wolff, Alexander; Mehranfar, Mahsa; Schmidt, Julia; Choudhary, Dharmendra; Gutiérrez-Gutiérrez, Óscar; Cyganek, Lukas; Saint-Dic, Djenann; Zibat, Arne; et al. (The journal of clinical investigation, 2025)
As a major component of intracellular trafficking, the coat protein complex II (COPII) is indispensable for cellular function during embryonic development and throughout life. The 4 SEC24 proteins (A–D) are essential COPII components involved in cargo selection and packaging. A human disorder corresponding to alterations of SEC24 function is currently known only for SEC24D. Here, we reported that biallelic loss of SEC24C leads to a syndrome characterized by primary microcephaly, brain anomalies, epilepsy, hearing loss, liver dysfunction, anemia, and cataracts in an extended consanguineous family with 4 affected individuals. We showed that knockout of sec24C in zebrafish recapitulated important aspects of the human phenotype. SEC24C-deficient fibroblasts displayed alterations in the expression of several COPII components as well as impaired anterograde trafficking to the Golgi, indicating a severe impact on COPII function. Transcriptome analysis revealed that SEC24C deficiency also affected the proteasome and autophagy pathways. Moreover, a shift in the N-glycosylation pattern and deregulation of the N-glycosylation pathway suggested a possible secondary alteration of protein glycosylation, linking the described disorder with the congenital disorders of glycosylation.